A system dynamics model to assess the interrelationship between different knowledge areas of PMBOK in a construction project - Zainab, A Malik (2018)
Successful construction projects are difficult to achieve in the dynamic and complex construction industry. Successful project management requires the application of knowledge areas in project management while managing projects and completing projects as scheduled. The Project Management Institute (PMI) has issued ten areas of knowledge that are interconnected with each other as a guide to project management. It has also explained step by step clearly for every area of knowledge in the Project Management Body of Knowledge (PMBOK). Existing research has focused on these areas of knowledge, either separately or individually to solve problems in a project. This situation can cause results taken in one area of knowledge to bring problems to other knowledge areas because the areas of knowledge related to the problem are seen separately. Therefore, this study was set up to solve the problem of project managers who made ineffective decision making due to looking at areas of knowledge related separately with the proposal to identify the connectivity and the relationship between different knowledge areas of PMBOK in construction projects. The areas of knowledge used in this study are procurement management, scope management, stakeholder management, integrated management, and human resource management. These five areas of knowledge are derived from a case study. Then, a causal loop is constructed to see the relationship between the knowledge field and is translated into stock and flow diagrams to develop a system dynamic model. After that, the system dynamic model was built and the model was tested. Only then, the required information is included and the recommendation strategy is formulated. Through the system dynamic model, project managers can link between different and relevant areas of knowledge, simulate and view them in larger descriptions. Simulation explains the behavior of the project and its relation to the pre-construction project process with different areas of knowledge in project management. After analyzing all the important data using the system dynamic model, it was found that pre-construction projects had been postponed around 38.7% from the schedule. This is due to several activities that can be done simultaneously, but done one by one. Additionally, project managers put inadequate number of employees to complete the project as scheduled. Through the system dynamic model, models can suggest possible strategies for reducing project completion time by combining several activities that can be carried out simultaneously and increase the number of employees sufficient to complete the project in a given time. Finally, the system dynamic model in this study can show forecasts if the results of the combined activities and the employees are added, the problem of completion of the project completion can be reduced.